Makna Dan Fungsi Simbol Biologika menurut Budaya Masyarakat Dayak Ngaju di Museum Balanga Palangka Raya - Lastaria Lastaria; Muhammad Tri Ramdhani; Indah Tri Handayani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Symbols are part of a complex means of communication that has various meanings. Symbols are not only in the form of verbs but symbols are also nonverbal as those found in customary practices are realized in the form of equipment/ objects/goods. This study aims to describe the meaning and function of the symbol of the cultural biology of the Ngaju Dayak community in the Balanga Museum Palangka Raya. The method used in this study is descriptive with a qualitative approach. The techniques used are recording, interviews, observation, and documentation. Based on the results of the study there are eight biological objects that contain cultural symbols for the Dayak Ngaju community, namely: dawen sawang (sawang leaves, uwei (rattan), humbang (bamboo), tampung papas (sacred leaves/purification), suli (galangal stems), creepers (clothes baskets), hadangan (buffalo), and maharanda.